Highly efficient removal of Cu(ii) by novel dendritic polyamine–pyridine-grafted chitosan beads from complicated salty and acidic wastewaters. Issue 34 (27th May 2020) - Wang, Li-Li; Ling, Chen; Li, Bang-Sen; Zhang, Da-Shuai; Li, Chen; Zhang, Xiao-Peng; Shi, Zai-Feng
Abstract : Dendritic polyamine chitosan (CNP) beads containing 2-aminomethyl pyridine were facilely prepared for the efficient removal of Cu(ii ) ions from highly acidic and salty solutions. Abstract : In this study, dendritic polyamine chitosan beads with and without 2-aminomethyl pyridine were facilely prepared and characterized. Compared to CN (without the pyridine function), more adsorption active sites, larger pores, higher nitrogen content, higher specific surface area, and higher strength could be obtained for CNP (with the pyridine function). CNP microspheres afforded a larger adsorption capacity than those obtained by CN for different pH values; further, the uptake amounts of Cu(ii ) were 0.84 and 1.12 mmol g −1 for CN and CNP beads, respectively, at pH 5. The CNP microspheres could scavenge Cu(ii ) from highly acidic and salty solutions: the maximum simulated uptake amount of 1.93 mmol g −1 at pH 5 could be achieved. Due to the strong bonding ability and weakly basic property of pyridine groups, the adsorption capacity of Cu(ii ) at pH 1 was 0.75 mmol g −1 in highly salty solutions, which was comparative to those obtained from the commercial pyridine chelating resin M4195 ( Q Cu(II) = 0.78 mmol g −1 at pH 1). In addition, a distinct salt-promotion effect could be observed for CNP beads at both pH 5 and 1. Therefore, the prepared adsorbent CNP beads can have promising potential applications in the selective capturing of heavy metals in complex solutions with higher concentrations of H + and inorganic salts, such as wastewaters from electroplating liquid and battery industries.